Architectural Design and Test Case Analysis of a Simulator for Failure Localization - Lu, Xiangzhu (University of Waterloo, 2024)
Failure localization involves identifying the suspicious locations of failures by analyzing the reported alarms recorded in the OTN control plane. To expedite the development of failure localization algorithms and reduce costs, a simulator is essential to replicate alarm propagation behaviors across various scenarios. This thesis presents the design and implementation of a simulator comprising the following components: a rule database, a topology generator, a failure generator, and an alarm generator. The topology generator produces network topologies to simulate various network conditions, while the failure generator generates simulated failures. Subsequently, the alarm generator utilizes the rule database to generate corresponding alarm data. The generated data structures include failures/alarms, alarm flows, alarm chains, and alarm correlation trees. Additionally, two post-processing methods are introduced to illustrate the derivation of new data structures from existing data. To validate the accuracy of the simulator, five test cases are introduced, featuring different topology settings, varying numbers of failures, and including a specific scenario involving noisy alarms.
Keywords: Optical Transport Network (OTN); failure localization; OTN-based simulator